2019
DOI: 10.1007/s11869-019-00684-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the tools to monitor air pollution in the Spanish ports system

Abstract: In general, seaports are located in urban areas or in their environs, whereby their activity has a very direct effect on the population. Therefore, reducing environmental contamination and improving air quality are priority management goals for port authorities (PAs). In Spain, the state-owned seaport system consists of 28 PAs that manage 46 ports. Its regulation received a major impulse through the enactment of the Spanish Ports Law in 2010. The law establishes especially the obligation that, annually, the PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Previous studies have proved that obtaining air quality information by deploying a large number of detectors is a prerequisite and necessary condition for air quality assessment and improvement [ 37 , 38 , 39 , 40 , 41 ]. However, strong correlations may exist between the PM 10 concentration data measured by devices arranged within a specific range [ 38 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have proved that obtaining air quality information by deploying a large number of detectors is a prerequisite and necessary condition for air quality assessment and improvement [ 37 , 38 , 39 , 40 , 41 ]. However, strong correlations may exist between the PM 10 concentration data measured by devices arranged within a specific range [ 38 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, there is an important paradox, because even though the relevance of an environmental management of ports is well known [5][6][7], the pressure to ensure competitiveness and globalization [8] represents a managerial stress; that is to say, the need to prioritize the environment sometimes prevents ports from maintaining economic efficiency [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that economic efficiency achieves its ideal target when ports have a high pro-environmental attitude, implementing proactive green policies [9]. The importance of knowing about external pressures on issues related to environmental management [5,12] and economic efficiency [7,9,10] is also widely recognized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the potential effects on the health of nearby residents [12][13][14][15], the environmental impact of port activities has become one of the main challenges of port development [16]. This fact has compelled the need to monitor PM concentrations in and near dry bulk ports, to design mitigation measures aimed at the green and sustainable development of the port [17][18][19].…”
Section: Introductionmentioning
confidence: 99%